Live and let die: insights into pseudoenzyme mechanisms from structure. (December 2017) - Murphy, James M; Mace, Peter D; Eyers, Patrick A
Graphical abstract: Highlights: Pseudoenzymes are structural, but catalytically defective, homologs of enzymes. Examples of pseudoenzymes have been identified in all kingdoms of life. Pseudoenzymes regulate metabolic and signalling enzymes and processes. They function allosterically, as signal integrators, scaffolds, and competitors. Structural biology is helping to drive a 'pseudoenzyme revolution'. Abstract : Pseudoenzymes were first described more than 50 years ago, when it was recognised that a subset of proteins that are structurally homologous to active enzymes lack amino acids necessary for catalytic activity. Recently, interest in pseudoenzymes has surged as it has become apparent that they constitute ∼10% of proteomes and perform essential metabolic and signalling functions that can be experimentally distinguished from catalytic outputs of enzymes. Here, we highlight recent structural studies of pseudoenzymes, which have revealed the molecular basis for roles as allosteric regulators of conventional enzymes, as molecular switches and integrators, as hubs for assembling protein complexes, and as competitors of substrate availability and holoenzyme assembly. As structural studies continue to illuminate pseudoenzyme molecular mechanisms, we anticipate that our knowledge of the breadth of their biological functions will expand in parallel.